Comparisons Concerning the Evolution of Tax Revenues - Romania - European Union (EU-27). Elements of Analysis - Florina POPA (Communications of International Proceedings, 2023)
This paper aims to analyze the evolution of Romania's tax revenues, compared to the EU-27 average, by tax base categories - labour, capital, consumption - expressed as a share in GDP and in total tax revenues, over a period of thirteen years, respectively, 2009-2021. The motive behind the study lies in the importance of studying the evolution of Romania's tax revenues, compared to the EU-27 average, by tax base categories - labour, capital, consumption - expressed as a share in GDP and in total tax revenues, over a period of thirteen years, respectively, 2009-2021. The intention of originality lies in the analysis itself, tackled in this study, which follows the results related to the elements that distinguish Romania in comparison to European Union (EU-27), in the evolution of Romania's fiscal revenues, by three tax base categories announced above, on the period 2009-2021. The methodology in the study was the research from foreign and domestic literature, processing of ideas through the author's own interpretation, the collection of the statistical database, analysis of the announced elements, in order to highlight the results obtained. Findings reflects the synthesis of ideas resulted from data analyzed and the results obtained from the study on the distribution of tax revenues according to the type of tax base - comparison Romania – EU-27.
Keywords: analysis; tax base; fiscal policy; budget; comparison Romania - EU-27